What Helping Babies Breathe knowledge and skills are formidable for healthcare workers? - Patel, Archana B.; Bang, Akash; Kurhe, Kunal; Bhargav, Savita; Hibberd, Patricia L. (Frontiers in Pediatrics, 2023)
Abstract Introduction: Most neonatal deaths occur in the first week of life, due to birth asphyxia. Helping Babies Breathe (HBB), is a simulation-based neonatal resuscitation training program to improve knowledge and skills. There is little information on which knowledge items or skill steps are challenging for the learners. Methods: We used training data from NICHD’s Global Network study to understand the items most challenging for Birth Attendants (BA) to guide future curriculum modifications. HBB training was provided in 15 primary, secondary and tertiary level care facilities in Nagpur, India. Refresher training was provided 6 months later. Each knowledge item and skill step was ranked from difficulty level 1 to 6 based on whether 91-100%, 81-90%, 71-80%, 61-70%, 51-60% or <50% of learners answered/performed the step correctly. Results: The initial HBB training was conducted in 272 physicians and 516 midwives of which 78 (28%) physicians and 161 (31%) midwives received refresher training. Questions related to timing of cord clamping, management of a meconium-stained baby, and steps to improve ventilation were most difficult for both physicians and midwives. The initial steps of Objective Structured Clinical Examination (OSCE)-A i.e. equipment checking, removing wet linen and immediate skin-to-skin contact were most difficult for both groups. Midwives missed stimulating newborns while physicians missed cord clamping and communicating with mother. In OSCE-B, starting ventilation in the first minute of life was the most missed step after both initial and 6 months refresher training for physicians and midwives. At the retraining, the retention was worst for cutting the cord (physicians level 3), optimal rate of ventilation, improving ventilation & counting heart rate (midwives level 3), calling for help (both groups level 3) and scenario ending step of monitoring the baby and communicating with mother (physicians level 4, midwives 3). Conclusion: All BAs found skill testing more difficult than knowledge testing. The difficulty level was more for midwives than for physicians. So, the HBB training duration and frequency of retraining can be tailored accordingly. This study will also inform subsequent refinement in the curriculum so that both trainers and trainees will be able to achieve the required proficiency.